2012
DOI: 10.1186/1756-0500-5-94
|View full text |Cite
|
Sign up to set email alerts
|

Genome skimming identifies polymorphism in tern populations and species

Abstract: BackgroundTerns (Charadriiformes: Sterninae) are a lineage of cosmopolitan shorebirds with a disputed evolutionary history that comprises several species of conservation concern. As a non-model system in genetics, previous study has left most of the nuclear genome unexplored, and population-level studies are limited to only 15% of the world's species of terns and noddies. Screening of polymorphic nuclear sequence markers is needed to enhance genetic resolution because of supposed low mitochondrial mutation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…For instance, the uncertainty in the position of Gygis in the trees recovered by Jackson et al . () was attributable to conflict between the different genes, but was also influenced by incomplete taxon sampling among Lari.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the uncertainty in the position of Gygis in the trees recovered by Jackson et al . () was attributable to conflict between the different genes, but was also influenced by incomplete taxon sampling among Lari.…”
Section: Methodsmentioning
confidence: 99%
“…Our goal here was to decipher the phylogenetic relationships among noddies, rather than testing the position of Gygis and noddies among other members of the Laridae, which would have required much larger taxon sampling. For instance, the uncertainty in the position of Gygis in the trees recovered by Jackson et al (2012) was attributable to conflict between the different genes, but was also influenced by incomplete taxon sampling among Lari.…”
Section: Methodsmentioning
confidence: 99%
“…Whether genome skimming, which has been successfully applied using fresh plant and animal tissues (e.g. Jackson, Emslie & Tuinen, ; Bock et al ., ), will also be successful using a range of herbarium specimens (with regard to both phylogenetic diversity and specimen age) has not been rigorously tested so far, and is the subject of this study. We also explore the relationship between nuclear genome size ( C value) and assembled plastome coverage, which, when using genome skimming, can be hypothesized to affect read coverage of organelle genome sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, molecular systematists (Thibault & Cibois 2017) and list-makers (Gill & Donsker 2019) have seized upon the Yeung et al (2009) study to make generalisations that dismiss other lines of evidence. However, the findings of Jackson et al (2012) suggest that fresh research, including both nuclear and mitochondrial genes, is sorely needed in this complex before genetic data can be seriously weighed against seemingly overwhelming non-molecular evidence. For now, the only meaningful taxonomy is to regard G. alba, G. candida and G. microrhyncha as biological species.…”
Section: Vocalisationsmentioning
confidence: 99%
“…The eclectic study of Thomas et al (2004), with a different molecular dataset, considered microrhyncha a species. Subsequently, Jackson et al (2012) showed that molecular studies of Charadriiformes that depend entirely on mitochondrial DNA can be problematic and would profit from additional nuclear markers. No such study has yet been published.…”
mentioning
confidence: 99%